Challanges Encountred By Visually Impaired Children And Their Teachers In Inclusive Primary Schools - Rout, Sarat Kumar; Behera, Narayan Prasad (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the multiple challenges encountered by visually impaired children (VIC) and their teachers in inclusive schools which have been a stumbling block on children who are in pursuit of knowledge and on teachers who facilitate learning. Further, the main focus of the paper is on some recommendations for the stakeholders to overcome these challenges. The study employs the descriptive survey method by involving the quantitative approach, though some aspects are dealt with qualitatively. A total of 90 participants were involved in the study. They were selected through simple random and purposive sampling techniques. Data were collected both from primary and secondary sources. Findings reveal overcrowded classes and shortage of assistive devices and trained teachers as major challenges faced; while lack of training, unavailability of teaching- learning materials, inappropriate methods and allocation of insufficient time for teaching/learning activities as other challenges. The study recommends provision of barrier free learning environment, adequate disabled-specific teaching-learning materials and assistive devices to VIC; appropriate monitoring and supervision mechanism to ensure the status of the resources and classroom practices; and the urgent need to introduce a core course on the philosophy and pedagogy of inclusive education to the teacher-trainees.